2014
DOI: 10.3892/mmr.2014.2967
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of stem cells derived from rat fascia: In vitro proliferative and multilineage potential assessment

Abstract: Fascia‑derived stem cells (FDSCs) were previously isolated from the fascia of the gluteus maximus of the rat. However, the use of FDSCs as a cell source for musculoskeletal tissue engineering has not been compared with that of adipose‑derived stem cells (ADSCs) and bone marrow‑derived mesenchymal stem cells (BMSCs). Therefore, the present study aimed to compare the mesenchymal stem cell (MSC) and self‑renewal stem cell markers, proliferative capacity and multilineage differentiation potential of these stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Li et al reported that cells isolated from epimysial and perimysial fasciae of the rat gluteus maximus have only chondrogenic potential. Wong et al observed that this epimysial type of fascial cells possess high chondrogenic but low osteogenic and adipogenic differentiation . These two studies are inconsistent, and distinct from our observations, possibly because the fascial cells they tested were from muscle epimysium and perimysium, and were subject to serial subcultures.…”
Section: Discussioncontrasting
confidence: 83%
“…Li et al reported that cells isolated from epimysial and perimysial fasciae of the rat gluteus maximus have only chondrogenic potential. Wong et al observed that this epimysial type of fascial cells possess high chondrogenic but low osteogenic and adipogenic differentiation . These two studies are inconsistent, and distinct from our observations, possibly because the fascial cells they tested were from muscle epimysium and perimysium, and were subject to serial subcultures.…”
Section: Discussioncontrasting
confidence: 83%
“…Wong et al explored the characteristics of rat fascia‐derived stem cells (Wong et al, ). Cells were isolated from rat fascia and stimulated to differentiate into the chondrogenic, osteogenic, and adipogenic lineage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that preservation of the fascia reduces the incidence of postoperative lymphoedema after lymph node dissection ( 27 ) and leads to fewer seromas, less time until drain removal, drain output and shorter hospital stay after abdominoplasty ( 28 ). In addition, fascia-derived stem cells may represent a source for musculoskeletal tissue repair ( 29 ) and it has been shown that scars are more severe when the fascia is injured surgically ( 30 ).…”
Section: Discussionmentioning
confidence: 99%